Adaptive Maximum Power Point Finding Using Direct V OC /2 Tracking Method With Microwatt Power Consumption for Energy Harvesting - Chew, Zheng Jun; Zhu, Meiling (IEEE transactions on power electronics, 2018)
Maximum power transfer occurs in many energy harvesters at their half open-circuit voltage (VOC /2). A novel implementation method of maximum power point finding based on the VOC /2 method is presented by exploiting the capacitor charging voltage across a smoothing capacitor connected in parallel with the energy harvester. The presented technique has a specifically designed high-pass filter, which has a peak output voltage that corresponds to the VOC /2 of the energy harvester. The control circuit filters and differentiates the voltage across the smoothing capacitor to directly determine the timing of reaching the VOC /2 of the energy harvester without having to find the VOC first and is fully implemented using discrete analog components without the need of a programmable controller, leading to low power consumption of the method. In this paper, the control circuit is used in conjunction with a full-wave diode bridge rectifier and a dc-dc converter to harvest energy from a piezoelectric energy harvester (PEH) as the studied case. The PEH was subjected to various strain levels at low frequencies from 2 to 10 Hz. Experimental results show that the implemented circuit is adaptive to various vibration amplitudes and frequencies and has a maximum power point finding efficiency of up to 98.28% with power consumption as low as 5.16 μW.